Contributions of mutation and selection to regulatory variation: lessons from the Saccharomyces cerevisiae TDH3 gene - Wittkopp, Patricia J. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2023)
Heritable variation in gene expression is common within and among species and contributes to phenotypic diversity. Mutations affecting either cis - or trans -regulatory sequences controlling gene expression give rise to variation in gene expression, and natural selection acting on this variation causes some regulatory variants to persist in a population for longer than others. To understand how mutation and selection interact to produce the patterns of regulatory variation we see within and among species, my colleagues and I have been systematically determining the effects of new mutations on expression of the TDH3 gene in Saccharomyces cerevisiae and comparing them to the effects of polymorphisms segregating within this species. We have also investigated the molecular mechanisms by which regulatory variants act. Over the past decade, this work has revealed properties of cis - and trans -regulatory mutations including their relative frequency, effects, dominance, pleiotropy and fitness consequences. Comparing these mutational effects to the effects of polymorphisms in natural populations, we have inferred selection acting on expression level, expression noise and phenotypic plasticity. Here, I summarize this body of work and synthesize its findings to make inferences not readily discernible from the individual studies alone. This article is part of the theme issue ‘Interdisciplinary approaches to predicting evolutionary biology’.